COVFIT HEALTH MOBILE APPLICATION - ISMAIL, NAJIHAH (IRC, 2020)
Mobile phone have become greatly significant for many people throughout the world. The ability easy access and portability makes it convenient for the user to use it anywhere and anytime. Currently, pandemic crisis of Covid-19 has increase the demand of digital access in every aspects due to reduce social interact with people. All over the world have taken mandatory preventive measure where all people must have temperature screening before entering a building or crowded places and also record of places each people have travel in the past 14 day. There are some cases that, an individual is declare fever from the temperature screening without any symptom. Therefore, to cater this mater an individual need to keep in track with their resting heart rate where heart rate will change if there are changes in body temperature. I feel like mostly people does not have their personal heart rate monitor to record their daily personal resting heart rate and also they keep on forgetting the place that they have travel in the past 14 days. Therefore, I proposing a mobile application, name CovFit Health to solve the following issue. Survey was done to gather information and requirements needed to build this app. The proposed app will be built to be running on both Android platform and iOS platform by using Flutter and Dart. Findings suggest that this application can solve the problem of Covid-19 personal health tracking. As conclusion, this application improve the users experience in track daily resting heart rate and travel path by using digital access through mobile phone.